2012
DOI: 10.1021/ic301374z
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Platinum(II) Complexes Containing Platinum-Based Moieties of Present Platinum Drugs and Furoxan Groups as Nitric Oxide Donors: Synthesis, DNA Interaction, and Cytotoxicity

Abstract: Six novel platinum(II) complexes 1-6 bearing different furoxan moieties as nitric oxide (NO) donors have been designed, synthesized, and characterized by elemental analysis and (1)H NMR, IR, and ESI-MS spectroscopy. The furoxan groups were introduced to the platinum complexes to release NO, which may take synergic action with the platinum-based moieties on the tumor cells. It was found that all compounds exhibited considerable cytotoxicity against human HCT-116 and SGC-7901 cell lines via DNA binding together … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 47 publications
(63 reference statements)
0
33
0
Order By: Relevance
“…IR spectra (Nujol) were registered with a Shimadzu FTIR-8300 instrument. 1 H NMR spectra were recorded on a Bruker 300 Avance spectrometer, operating at 300 MHz, with tetramethylsilane (TMS) as an internal standard. The molar conductivities for all complexes were determined in DMSO at 10 −3 M at 25°C with a Crison GLP 31 Model Conductometer.…”
Section: General Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IR spectra (Nujol) were registered with a Shimadzu FTIR-8300 instrument. 1 H NMR spectra were recorded on a Bruker 300 Avance spectrometer, operating at 300 MHz, with tetramethylsilane (TMS) as an internal standard. The molar conductivities for all complexes were determined in DMSO at 10 −3 M at 25°C with a Crison GLP 31 Model Conductometer.…”
Section: General Methodsmentioning
confidence: 99%
“…Many efforts have been dedicated to explain the factors related to the anticancer activity of cisplatin and different platinum compounds [1,2] and although the molecular mechanistic studies of cisplatin and analogs have been largely developed, the cellular response to these compounds is still poorly understood [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The research of Zhao J et al found that hybrids of furoxan and Pt (4a, 4b, 4c, Figure 1) were more effective against gastric carcinoma cell line SGC-7901 and colonic carcinoma cell line HCT-116 in vitro compared with carboplatin, oxaliplatin alone or a combination of oxaliplatin and furoxan (23). Moreover, it was demonstrated that the hybrids had better stability and less adverse effects than Platinum agents (24).…”
Section: No Donors-pt Hybridsmentioning
confidence: 98%
“…), [7][8][9] including the 1,2,5-oxadiazole 2-oxides (furoxans) which are capable of exogenous NO release at the presence of thiol cofactors. 10,11 Furoxans comprise a valuable class of five-membered heterocycles and can serve as a privileged motif in medicinal and pharmaceutical chemistry owing to their significant biological activities, for example neuroprotective and precognitive, 12 cytotoxic, 13,14 antihelmintic, 15 antibacterial 16 and fungicidal 17 , connected with the high capacity of furoxans to produce a large flux of NO. It was established that NO exerts a cytotoxic effect at high concentrations, while low levels of NO are potentially protective, particularly in the CNS.…”
Section: Introductionmentioning
confidence: 99%
“…Various derivatives of these types of heterocycle have previously revealed cytotoxic activity: 1,2,4-oxadiazole, 31 1,2,4-triazine, 32,33 1,2,3-triazole, 34 and furoxan itself. 13,14 Heterocyclic motifs, namely quinolines 35 and pyridines, 36 connected to the furoxan ring through O-bridges, are also found in compounds possessing cytotoxic activity.…”
Section: Introductionmentioning
confidence: 99%